Law and Finance in Britain c.1900 - Christopher Coyle; Aldo Musacchio; John D. Turner (Queen's University Belfast, Queen's Management School, 2019)
In this paper, using new estimates of the size of the UK's capital market, we examine financial development and investor protection laws in Britain c.1900 to test the influential law and finance hypothesis. Our evidence suggests that there was not a close correlation between financial development and investor protection laws c.1900 and that the size of the UK's share market is a puzzle given the paucity of statutory investor protection. To illustrate that Britain was not unique in its approach to investor protection in this era, we examine investor protection laws across legal families c.1900
Keywords: G3; G33; K22; N20; 330